2015
DOI: 10.1161/circulationaha.115.017364
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Coated Balloon Versus Standard Balloon for Superficial Femoral Artery In-Stent Restenosis

Abstract: Background-Drug-coated balloon angioplasty (DCBA) was shown to be superior to standard balloon angioplasty (POBA) in terms of restenosis prevention for de novo superficial femoral artery disease. For in-stent restenosis, the benefit of DCBA over POBA remains uncertain. Methods and Results-One hundred nineteen patients with superficial femoral artery in-stent restenosis and chronic limb ischemia were recruited over 34 months at 5 German clinical sites and prospectively randomized to either DCBA (n=62) or POBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(57 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…3,4 Many factors contribute to limitations on outcomes in the FP segment, including the complex mechanical forces placed on these vessels (e.g., compression, flexion, torsion), combined with the need for longer stents to cover lesions, leading to high rates of FP in-stent restenosis (FP-ISR). [5][6][7] The incidence of FP-ISR varies by stent type, but is between 19% and 37% at 12 months, 50% at 24 months, and 60% at 36 months. 4,5,8 Among current treatment options for FP-ISR, balloon angioplasty (BA) alone has yielded poor results, with under 50% primary patency 6 months following revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Many factors contribute to limitations on outcomes in the FP segment, including the complex mechanical forces placed on these vessels (e.g., compression, flexion, torsion), combined with the need for longer stents to cover lesions, leading to high rates of FP in-stent restenosis (FP-ISR). [5][6][7] The incidence of FP-ISR varies by stent type, but is between 19% and 37% at 12 months, 50% at 24 months, and 60% at 36 months. 4,5,8 Among current treatment options for FP-ISR, balloon angioplasty (BA) alone has yielded poor results, with under 50% primary patency 6 months following revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 summarizes studies and registries containing data about DCB use in ISR lesions (lesion length: 81–137 mm) in the SFA 3135. The number of diabetic and CLI patients was higher than in the herein-cited studies (up to 100% diabetics in DEBATE ISR35 and 67%–75% CLI in the FAIR34 and the COPA CABANA trials 33. At 12 months, all studies showed promising TLR rates after DCB treatment compared to the respective uncoated control (Figure 5).…”
Section: Dcb Use In Isr Lesions Of the Sfamentioning
confidence: 91%
“…In ISR, recent studies showed superior results for DCBs, with TLR rates for DCB of 9.2% and 30% which were significantly lower than those for appropriate standard PTA, with 47% and 63%, respectively 33,34. Potential alternative endovascular treatment options for ISR, apart from balloon angioplasty (PTA), are brachytherapy, cutting or scoring balloon technique, cryoplasty, and repeated stenting with a nitinol stent, stentgraft, or DES 63.…”
Section: Are Dcbs the Best Treatment Method? For Sfa? For Btk? For Isr?mentioning
confidence: 99%
“…Drug-coated balloons also prevent restenosis when used prior to bare-metal stent deployment 28 , and offer more durable treatment of instent restenosis of the femoral artery 29 . The evidence supporting drug-eluting stents and drug-coated balloons is much stronger than for covered-self expanding stents, which have uncertain effects on restenosis and stent thrombosis 30 .…”
Section: Endovascular Revascularizationmentioning
confidence: 99%